PENINGKATAN HASIL BELAJAR TRIGONOMETRI MELALUI PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE (TPS) SISWA KELAS X IPS 2 SMA NEGERI 1 MAUMERE - MARIA SALESTINA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Cooperative learning is learning with class settings that are made in groups, which intend to be able to help students in the process of knowledge construction, because in addition to students learning with the teacher, students also learn together with friends in small groups. While the Think-Pair-Share (TPS) type of cooperative learning model is learning with a structural approach (PS) where students are placed in heterogeneous learning groups with 2 members or pairs. This study aims to determine the increase in trigonometric learning outcomes of students of class X IPS 2 of SMA Negeri 1 Maumere with cooperative learning Think-Pair -Share type. This type of research is qualitative research and quantitative research with classroom actions research. The research subjects were students of class X IPS 2 of SMA Negeri 1 Maumere in the academic year 2017/2018 totaling 36 students. The instruments used were test questions and observation sheets. Based on the results of the study, it was found that the Think Pair Share (TPS) type of cooperative learning model could improve student learning outcomes in class X IPS 2 of SMA Negeri 1 Maumere on trigonometry material. This can be demonstrated by an increase in test results starting from the end of the first cycle to the end of the third cycle. At the end of the first cycle test, values> 75 were 16 students (44.4%). In cycle II there was also an increase in which students scored> 75 by 23 students (63.8). Then in cycle III there was an increase in the number of students who scored> 75 by 29 students (80.5%).